THE ROLE OF DISTANCE EDUCATION IN THE IMPLEMENTATION OF STRATEGIES OF GENERAL SECONDARY EDUCATION - Rustam Salimovich Odilov (Bright Mind Publishing, 2025)
This article analyzes the role of distance education in the implementation of general secondary education strategies. Distance education, based on modern technologies, helps make the educational process more flexible, convenient, and effective. The study highlights the importance of distance education for both learners and teachers, its advantages, as well as the challenges encountered. Through surveys and analysis of scientific literature, the effectiveness of distance education is evaluated. The article examines the role of distance learning in students' educational processes, its contribution to improving the quality of education, and issues related to digital transformation in the education system. The research findings emphasize the importance of developing technological infrastructure, enhancing teachers' professional qualifications, and fostering learners' independent learning skills for the effective use of distance education.
Keywords: Distance education, digital learning, secondary education strategy, online learning, pedagogy, innovative teaching methods, educational effectiveness, interactive learning.